2017
DOI: 10.1158/0008-5472.can-17-1569
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing in the Clinical Setting Clarifies Patient Characteristics and Potential Actionability

Abstract: Enhancements in clinical-grade next-generation sequencing (NGS) have fueled the advancement of precision medicine in the clinical oncology field. Here we survey the molecular profiles of 1,113 patients with diverse malignancies who successfully underwent clinical-grade NGS (236 to 404 genes) in an academic tertiary cancer center. Among the individual tumors examined, the majority showed at least one detectable alteration (97.2%). Amongst 2,045 molecular aberrations was involvement of 302 distinct genes. The mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…1,7 The advent of next-generation sequencing has unearthed diverse genomic aberrations that are associated with different cancer types. [8][9][10][11][12] Specifically, recent deep sequencing analysis has revealed that 4.4% of tumors carry GNAS aberrations. 1 Several studies have shown that GNAS aberrations span a wide variety of endocrine tumors, including those originating from the pituitary (28%), pancreas (12%), thyroid (5%), and parathyroid (3%), ovary (3%), endometrium (2%).…”
Section: Introductionmentioning
confidence: 99%
“…1,7 The advent of next-generation sequencing has unearthed diverse genomic aberrations that are associated with different cancer types. [8][9][10][11][12] Specifically, recent deep sequencing analysis has revealed that 4.4% of tumors carry GNAS aberrations. 1 Several studies have shown that GNAS aberrations span a wide variety of endocrine tumors, including those originating from the pituitary (28%), pancreas (12%), thyroid (5%), and parathyroid (3%), ovary (3%), endometrium (2%).…”
Section: Introductionmentioning
confidence: 99%
“…Intrapatient variability, with changes in the molecular profile from primary to metastatic disease and over the course of treatment, presents challenges to personalized medicine. [13][14][15][16] Furthermore, some authors have even attempted to classify potentially actionable alterations into categories with little success due to the rapidly evolving technology and knowledge. 17 Published results vary widely depending on tissue type, but 39%-83% are predicted to have a mutation for which matched therapy exists.…”
Section: Discussionmentioning
confidence: 99%
“…1 Even with shared histopathologies or organ of origin, genomics has unveiled a remarkably complicated biologic landscape, with metastatic malignancies manifesting molecular complexity that differs from tumor to tumor. [2][3][4] In order to impact heterogeneous cancers in a precise manner, one must customize (or personalize) the therapeutic regimen. This new precision-personalized model differs from conventional strategies for cancer management in that it reflects a patientcentric, rather than drug-centric approach.…”
Section: Perspectivementioning
confidence: 99%